Application of Honey Therapy to Decrease Stool Frequency in Children with Diarrhea: A Case Study - Nehemia Mutiara Saragih; Kurniawati Kurniawati; Nia Khusniyati; Fathul Jannah (Journal of Health Sciences and Epidemiology, 2023)
Diarrhea is characterized by the presence of watery bowel motions that occur three or more times within 24 hours. Inadequate management of diarrhea in children might lead to fatality. One method involves administering honey treatment to decrease the frequency of bowel movements. The objective was to elucidate the implementation of a way to reduce bowel movement frequency. The design involved a case study conducted on two toddlers suffering from diarrhea. The solution involved administering honey therapy three times daily for five days. Data analysis and presentation in case studies were conveyed through written text, which presented the facts in a narrative format. The use of honey therapy resulted in a reduction in the frequency of bowel movements in subjects 1 and 2. The post-intervention frequency of bowel movement in subject 1 was three times per day, with a mushy consistency. In subject 2, it was four times per day, again with a mushy consistency. Nurses at the Community Health Center (Puskesmas) can offer guidance on using honey therapy to parents whose children are suffering from diarrhea.